PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP LAMANYA WAKTU PENYELESAIAN AUDIT (AUDIT DELAY) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Puspitasari, Elen; Sari, Anggraeni Nurmala (JURNAL AKUNTANSI DAN AUDITING, 2012)
Audit delay or the completion of the audit period may affect the timeliness of the informationpublished and can affect the level of uncertainty that decision based on published information.Characteristic of the company is one of the factors that affect audit delay. This research aimed toexamine the influence of the characteristics of the company, which consists of company size,solvency, profit or loss company on audit delay in the manufacturing companies listed on theIndonesia Stock Exchange (IDX) by adding one variable that is thought to have an influence onaudit delay, i.e. the size of Public Accounting Firms. The entire manufacturing companies listed onthe IDX in 2007 to 2010 are population in this study. Purposive sampling technique is used toobtain the sample size by 69 manufacturing companies with the acquisition of observational data asmuch as 276. Multiple regression analysis is used to test hypotheses to explain the relationshipbetween the variables in this research. The results of the partial examination showed that allindependent variables are characteristics of the company consists of company size, solvency, profitor loss of the company, and the size of the Public Accounting Firms has a significant influence onaudit delay.Keywords:audit delay, characteristic of the company, company size, solvency, profit or loss, size of thepublic accounting firms